KEPEMIMPINAN BERBASIS EKOLOGIS DALAM PERSPEKTIF ISLAM (Studi Kasus di SD Alam Lampung) - Nanda Inka Fitri; Zahara; Qonita; Chairul Anwar; Syaiful Anwar; Wasehudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRAK This study examines the implementation of the "Learning with Nature" (Belajar Bersama Alam/BBA) method at SD Alam Lampung as a holistic educational approach that instills ecological-based leadership values. By integrating thematic learning, environmental exploration, and Islamic spiritual values, BBA shapes students' character as stewards (khalifah) of the Earth who are responsible for environmental sustainability. This concept is manifested through practical activities such as gardening, waste management, and outdoor learning, supported by the design of an environmentally friendly (green) school. The role of teachers as facilitators and the involvement of parents further strengthen the sustainable educational ecosystem. Interviews reveal that the BBA method is effective in fostering early leadership development in children with a strong ecological awareness, in line with the goals of character education and sustainability. Keywords: Learning with Nature, ecological leadership, SD Alam Lampung, character education, green school.